Mendorong Kepercayaan Diri Anak Madrasah Diniyah Sullamul Hidayah Melalui Seminar dan Pelatihan Public Speaking - Nur Hamda Sa’idah; Widya Arum Lestari; Muhammad Yusuf Saifullah; I’in Ustadhiyah; Sokhi Zuhrotunnisa; Maulidia Putri Anggraini; Susilo Wati; Riska Maulina; Hafidha Asni Akmalia (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2024)
Public speaking is an ability that a person has to be able to speak in public with the aim of conveying an idea or information. Public speaking is an important skill to have in this day and age. However, in reality, public speaking becomes a scary thing for some people. This is due to feelings of anxiety, fear, nervousness, and lack of confidence in their own abilities. The existence of public speaking seminars and training is expected to increase self-confidence and eliminate feelings of fear when faced with such situations. The activity entitled "Berani Bicara, Berani Berdakwah" was carried out with 3 stages, namely the preparation stage, the implementation stage, and the evaluation stage. From the activities that have been carried out at Madrasah Diniyah Takmiliyah Ula NU 08 Sullamul Hidayah, children can learn and dare to show public speaking skills during the event. Not only that, the children also began to control their negative feelings, such as fear, anxiety, and lack of confidence